(untitled) (Itinera, 2015)
The first part of the essay, Rationality of Improvisation, is developed through two complementary directions. On the one hand it traces the plot through which a specific determination of Western rationality has marked the art music tradition of modernity. On the other hand, it identifies a specific alternative cognitive modality, defined audiotactile, which is inherent to the formative creative practices in real time, showing how its constitutive incompatibility with the structural epistemic logic of Western rationality has led to the modern eclipse of the ex tempore creativity, and to its resurgence today. In the second part, Improvisation of Rationality, are discussed in a pragmatic perspective such aesthetic issues as improvisational freedom, the situational and stylistic conditioning and their relationship with the authenticity and with the aesthetic truth, and whether it is possible to identify prospects for a normativity in improvisation.